2000
DOI: 10.1046/j.1460-9568.2000.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Laterodorsal tegmental stimulation elicits dopamine efflux in the rat nucleus accumbens by activation of acetylcholine and glutamate receptors in the ventral tegmental area

Abstract: Cholinergic and glutamatergic neurons in the laterodorsal tegmentum (LDT) and neighbouring mesopontine nuclei are thought to influence mesolimbic dopaminergic neuronal activity involved in goal-directed behaviours. We measured the changes in dopamine oxidation current (corresponding with dopamine efflux) in the nucleus accumbens (NAc) in response to electrical stimulation of the LDT using in vivo chronoamperometry in urethane-anaesthetized rats. LDT stimulation (35 Hz pulse trains for 60 s, 1 s intertrain inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
233
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(255 citation statements)
references
References 75 publications
(71 reference statements)
21
233
0
1
Order By: Relevance
“…In support of this notion, it has been shown that acetylcholine levels in the VTA increase in response to feeding and drinking (Rada et al, 2000). Moreover, electrical or chemical stimulation of the pedunculopontine and laterodorsal tegmental nuclei (PPTg and LdTg), the brainstem nuclei containing acetylcholinergic neurons that send afferents to the VTA, induces burst firing of midbrain dopaminergic cells (Lokwan et al, 1999;Floresco et al, 2003) and increases dopamine release in the nucleus accumbens, in part by activating nAChRs and NMDA receptors in the VTA (Forster and Blaha, 2000). Our data suggest that under conditions of high cholinergic activity, acetylcholine may activate a7 nAChRs located on glutamatergic terminals to enhance glutamate release.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In support of this notion, it has been shown that acetylcholine levels in the VTA increase in response to feeding and drinking (Rada et al, 2000). Moreover, electrical or chemical stimulation of the pedunculopontine and laterodorsal tegmental nuclei (PPTg and LdTg), the brainstem nuclei containing acetylcholinergic neurons that send afferents to the VTA, induces burst firing of midbrain dopaminergic cells (Lokwan et al, 1999;Floresco et al, 2003) and increases dopamine release in the nucleus accumbens, in part by activating nAChRs and NMDA receptors in the VTA (Forster and Blaha, 2000). Our data suggest that under conditions of high cholinergic activity, acetylcholine may activate a7 nAChRs located on glutamatergic terminals to enhance glutamate release.…”
Section: Discussionmentioning
confidence: 91%
“…Another possibility could be that inhibition involving mAChRs occurs at the level of the LdTg. Increased levels of acetylcholine due to AChE inhibition in the LdTg might thus activate autoinhibitory mAChRs and, thereby, inhibit the activity of these cells (Luebke et al, 1993;Forster and Blaha, 2000) with a resulting decrease in the release of acetylcholine in the VTA. The fact that following the highest dose of galantamine there was no significant effect on firing rate or prefrontal dopamine output may be related to a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…All of these neurotransmitters excite VTA dopaminergic neurons (Gronier and Rasmussen, 1998;Forster and Blaha, 2000;Lejeune and Millan, 2000;Uramura et al, 2001) and, hence, are probably also excitatory in the vPAG.…”
Section: Technical Considerationmentioning
confidence: 99%
“…Of these, the descending excitatory amino acid projection from the PFC to the VTA has been particularly implicated in the induction of psychostimulant sensitization, because lesions of the PFC prevent the induction of locomotor sensitization by systemic and intra-VTA (Cador et al, 1999) AMPH. Interestingly, recent anatomical (Carr and Sesack, 2000), neurochemical (Takahata and Moghaddam, 2000), and electrophysiological (Lokwan et al, 1999) reports suggest that the PFC-VTA glutamatergic projection does not regulate VTA-NAcc DA neurons directly but rather via polysynaptic midbrain circuits using GABA, glutamate, acetylcholine, and perhaps other transmitters originating in the VTA and sites (eg pedunculopontine and laterodorsal nuclei; Lokwan et al, 1999;Forster and Blaha, 2000) projecting to it. The contribution of these local circuits as well as non-PFC originating glutamatergic afferents to the VTA to the enhancement of psychostimulant self-administration produced by previous exposure to AMPH remains to be elucidated.…”
Section: Induction Of Sensitization By Amph Requires Activation Of Glmentioning
confidence: 99%